Imaging properties and tumor targeting of 68Ga-NeoBOMB1, a gastrin-releasing peptide receptor antagonist, in GIST patients - Gruber, Leonhard; Decristoforo, Clemens; Uprimny, Christian; Hohenberger, Peter; Schönberg, Stefan; Orlandi, Francesca; Mariani, Maurizio Franco; Manzl, Claudia; Kasseroler, Maria Theresia; Tilg, Herbert; Zelger, Bettina; Jaschke, Werner; et al. (Biomedicines, 2022)
Background: Gastrin-releasing peptide receptors (GRPRs) are molecular imaging targets in multiple malignancies. Recently, NeoBOMB1, a 68Ga-labelled antagonist to GRPRs, was developed for PET. Here we report the outcome of a Phase I/IIa clinical trial (EudraCT 2016-002053-38) describing diagnostic properties and covariates influencing uptake of 68Ga-NeoBOMB1 in oligometastatic gastrointestinal stromal tumor (GIST) patients. Methods: Nine patients with advanced GIST using PET/CT (computed tomography) were included. After kit-based 68Ga-NeoBOMB1 preparation with a licensed 68Ge/68Ga generator, 3 MBq/kg body weight were injected intravenously. PET/CT included dynamic and static PET scans 5, 12 and 18 min and 1, 2, and 3-4 h post injection (first six patients) and static PET scans 2 and 3-4 h post injection (last three participants). Tumor targeting was assessed on a per-lesion and per-patient basis. Results: Six patients showed visible radiotracer uptake in at least one tumor lesion. Seventeen out of 37 tumor lesions exhibited significant 68Ga-NeoBOMB1 uptake (median SUVmax 11.8 [range 2.8-51.1] 2 h p.i. and 13.2 [range 2.5-53.8] 3-4 h p.i) and improved lesion-to-background contrast over time. Five lesions (13.5%) were identified only by 68Ga-NeoBOMB1-PET, with no correlation on contrast-enhanced CT. Three patients showed no radiotracer accumulation in any lesions. Tracer uptake correlated with male sex (p < 0.0001), higher body mass index (p = 0.007), and non-necrotic lesion appearance (p = 0.018). There was no association with whole-lesion contrast enhancement, hepatic localization, mutational status, or disease duration. Conclusions: 68Ga-NeoBOMB1-PET exhibits variable tumor uptake in advanced-stage GIST patients, correlating with lesion vitality based on CT contrast uptake, opening the possibility of a theragnostic approach in selected cases.
Im Titel ist die Zahl 68 hochgestellt
Gesehen am 18.01.2023